2017
DOI: 10.24896/easl2017427
|View full text |Cite
|
Sign up to set email alerts
|

Discoveries of Carpet Beetles (Coleoptera: Dermestidae) of the South of Russia

Abstract: SUMMARY. As a result of the collecting in 2003–2015 in the south part of European Russia and in the North Caucasus 15 species of the carpet beetles (Dermestidae) were found, which was firstly recorded for the Russian territory or was recently listed without specific information: Dermestes intermedius Kalik, 1951, Dermestes elegans Gebler in Ledebour, 1830,  Attagenus fasciolatus (Solsky, 1876), Anthrenus amoenulus Reitter, 1896, Anthrenus zebra Reitter, 1889, Anthrenus latefasciatus Reitter, 1892, Anthrenus ol… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

0
5
0

Year Published

2021
2021
2021
2021

Publication Types

Select...
1

Relationship

0
1

Authors

Journals

citations
Cited by 1 publication
(5 citation statements)
references
References 0 publications
0
5
0
Order By: Relevance
“…Beetles start breeding earlier in the semi-desert and steppe zones of the study area. The daily activity of most species falls under the description of morning-evening activity (8-10; 18-21 hours), D. bicolor is characterized by twilight activity (6-8; 19-22 hours) [9,41]. Encounters of adults, larvae, and pupae in nests in all seasons of the year are proof of their good adaptation to the nidicolous way of life (feeding, reproduction) in the specific conditions of the microbiocenosis of the host nest.…”
Section: Resultsmentioning
confidence: 99%
See 4 more Smart Citations
“…Beetles start breeding earlier in the semi-desert and steppe zones of the study area. The daily activity of most species falls under the description of morning-evening activity (8-10; 18-21 hours), D. bicolor is characterized by twilight activity (6-8; 19-22 hours) [9,41]. Encounters of adults, larvae, and pupae in nests in all seasons of the year are proof of their good adaptation to the nidicolous way of life (feeding, reproduction) in the specific conditions of the microbiocenosis of the host nest.…”
Section: Resultsmentioning
confidence: 99%
“…At present, more than 200 species of beetles are known for which infestation with helminth larvae has been established [3-7, 14-16, 26], which increases interest not only in clarifying the species composition of beetles but also in studying their biology as components of the nest microbiocenosis. For Dermestidae species, the possibility of transferring pathogens has been established [8,24,25]. Gamasids are phoresiaphoresizedtic on adults of necrobiont species; according to our research, the following species of gamasid mites have been identified -Poecilochirus necrophori, Parasitus ssp..…”
Section: Introductionmentioning
confidence: 81%
See 3 more Smart Citations